(untitled) (Research, Society and Development, 2021)
In dogs, the synthesis of vitamin D in the skin is considered inefficient, making dietary supplementation the main source of this vitamin for these animals. In humans, there are established values for 25-hydroxyvitamin D (25(OH)D) deficiency, insufficiency and sufficiency levels, however in dogs, the serum concentrations of these values are not well established. The purposes of this study were to evaluate the 25(OH)D serum levels in dogs carrying myoclonus as sequelae of distemper, to evaluate the response to vitamin D levels on oral supplementation, to evaluate PTH, calcium, phosphorus, alanine aminotransferase (ALT), aspartate aminotransferase (AST), blood count and leukogram levels, in addition to conduct clinical observations of myoclonus. Venous blood samples were collected from nine dogs carrying myoclonus derived from distemper, however with no other clinical or laboratorial change, of varied breeds and same age group (1 - 8 years old). Screening laboratory tests were performed to attest to the health of the animals in a 30-day period and the collections were divided into three periods: days 0, 15 and 30. After the initiation of treatment, the animals underwent physical and laboratorial evaluations every 15 days, for 90 days, completing a total of 120 days. The dose used for oral supplementation of vitamin D3 was 1000IU/kg administered every day, once a day, during the entire experimental period. For clinical evaluation, parameters of anatomical distribution, speed and rhythm, and distribution of myoclonic changes over time were observed. The laboratory results were subjected to analysis of variance and, when significant (P<0.05), submitted to regression analysis. Descriptive statistics were used to analyze clinical results. There was a significant difference in blood concentrations of 25(OH)D, PTH, calcium and phosphorus, however there was no significant effect of vitamin D on the other parameters evaluated. It was possible to conclude that the dose of vitamin D3 used was sufficient to increase 25(OH)D serum levels in the blood, to levels of sufficiency, having influence on PTH, phosphorus and calcium levels, not changing the other hematological and clinical parameters evaluated. However, the dose and duration of the treatment used did not change the myoclonus derived from distemper in dogs.